INTEGRATING STRATEGIC RISK MANAGEMENT AND SUSTAINABLE STRATEGIC PLANNING TO ENHANCE INDONESIAN LISTED BANKS’ FINANCIAL HEALTH - WIRDA MARDYANINGSIH; Rahma Febrianti; Akhmad Ghozali (TECHNOBIZ : International Journal of Business, 2025)
The banking sector plays a vital role in sustaining national economic stability but has faced major challenges in the past five years, including the Covid-19 pandemic and the growing pressure to adopt sustainability principles. The financial health of publicly listed banks, as key players in the financial system, depends on their ability to manage strategic risks and implement sustainable planning. This study investigates the effect of Strategic Risk Management (SRM) on Financial Health, with Sustainable Strategic Planning (SSP) as a mediating variable. A quantitative approach was applied using secondary data from 33 publicly listed banks in Indonesia during 2020–2024. SRM was measured through strategic risk disclosure and the integration of risk into business strategies. SSP was proxied by sustainability roadmaps, ESG policies, and the implementation of green strategies. Financial Health was assessed using CAR, NPL, ROA, LDR, and CIR ratios. The results indicate that SRM significantly improves SSP, SSP significantly enhances Financial Health, and SRM also directly affects Financial Health. Furthermore, SSP fully mediates the relationship between SRM and Financial Health. These findings highlight the importance of embedding strategic risk management into sustainable planning to strengthen the financial resilience of Indonesian banks